Transitions and Transformations in Learning and Education - Tynjälä, Päivi; Stenström, Marja-Leena.; Saarnivaara, Marjatta; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2012)
The breakneck speed of change in today’s societies creates enormous challenges for educational institutions at all levels. This volume explores ways  how to manage change in educational processes and contexts,  focusing, in particular, on the concepts of transition and transformation. How do we educate a skilled workforce, sensitive professionals and responsive citizens who are able not only to cope with change but also to adopt required roles as agents of change? How do we prepare students and employees to cope adequately with changes and transitions in their careers and personal lives? The first of this book’s three sections deals with the conceptual and theoretical aspects of transition, transformational processes and human development. It defines these concepts and examines the ways in which educational theory and praxis understand concepts of change and development. The second section presents empirical studies that offer differing perspectives on educational transitions, covering the lifespan from early years education to lifelong learning. The third part of the volume focuses on issues of learning and pedagogy and argues that educational practices should change with the changing world. With numerous concrete examples included in the analysis, and with studies taking a range of forms from personal histories to large-scale surveys, this new book is a major addition to the literature in a field that has key implications for our future.
PART I:   THEORETICAL ANALYSES OF CHANGE -- Introduction and Overview, Päivi Tynjälä, Marja-Leena Stenström, Marjatta Saarnivaara -- Chapter 01. The Coming of the Ecological Learner, Ronald Barnett -- Chapter 02. An Overview of the Concepts of Change and Development – from the Pre-Modern to Modern Era, Eeva Kallio, Helena Marchand -- Chapter 03. Transformations Towards Mature Thinking – Challenges for Education and Learning, Hanna-Maija Liitos, Eeva Kallio, Päivi Tynjälä -- Chapter 04. Transition and Constitution in the School/Work Relations, Matti Vesa Volanen -- PART II: TRANSITIONS IN EDUCATIONAL PATHS -- Chapter 05. Interprofessional Collaboration in Supporting Transition to School, Anneli Sarja, Pirjo-Liisa Poikonen, Monica Nilsson -- Chapter 06. Transitions in Individual Vocational Education Pathways – Challenges and Collaborative Solutions, Aini-Kristiina Jäppinen -- Chapter 07. Dropping Out from Apprenticeship Training as an Opportunity for Change, Evi Schmid, Barbara E. Stalder -- Chapter 08. Higher Education Graduates’ Employment and the Uncertainty of Working Life, Päivi Vuorinen, Marja-Leena Stenström -- Chapter 09. Motivation, Burnout and Engagement during Critical Transitions from School to Work, Katariina Salmela-Aro -- Chapter 10. The Induction Phase as a Critical Transition for Newly Qualified Teachers, Hannu Jokinen, Hannu L. T. Heikkinen, Åsa Morberg -- Chapter 11. Transformations in Lifelong Guidance Provision, Seija Nykänen, Sakari Saukkonen, Raimo Vuorinen -- PART III: LEARNING AND PEDAGOGY IN TRANSFORMATION -- Chapter 12. Changing World – Changing Pedagogy, Päivi Tynjälä, David Gijbels -- Chapter 13. Four Categories of Change Strategies for Transforming Undergraduate Instruction, Charles Henderson, Andrea Beach, Noah Finkelstein -- Chapter 14. Approaches to Transition Support for First Year Students in Higher Education, Sanna Honkimäki, Orsolya Kálmán -- Chapter 15. Mentoring as Dialogue, Collaboration and/or Assessment?, Jessica Aspfors, Göran Fransson, Hannu L. T. Heikkinen -- Chapter 16. Young Men in Digital Culture – a New Form of Informal Learning?, Kirsi Pohjola & Kimmo Jokinen -- Chapter 17. Transgressive Learning – a Possible Vista in Higher Education?, Marjatta Saarnivaara, Carolyn Ellis, Helka-Maria Kinnunen.
Keywords: Professional education; Vocational education; Higher education; Educational policy; Education and state; Professional & Vocational Education; Higher Education; Educational Policy and Politics